Osteosarcopenia in Very Old Age Adults After Hip Fracture: A Real-World Therapeutic Standpoint - Pizzonia, Monica; Casabella, Andrea; Natali, Marta; Petrocchi, Lorena; Carmisciano, Luca; Nencioni, Alessio; Molfetta, Luigi; Giannotti, Chiara; Bianchi, Gerolamo; Giusti, Andrea; Santolini, Federico; Monacelli, Fiammetta (Frontiers in Medicine, 2021)
Loss of bone and muscle mass and strength (i.e osteosarcopenia) is a highly prevalent clinical condition in older adults , associated with an increased risk of fragility fractures and unfavorable clinical outcomes,Although sarcopenia is a potential risk factor for osteoporosis and subsequent fracture, and the management of this hazardous duet is the key to preventing osteoporotic fracture, evidence pertaining to the treatment of sarcopenia for the purpose of preventing fragile fractures remains insufficient . Given this scenario we aimed at prospectively compare the long-term effectiveness of bisphosphonates versus denosumab, on bone and muscle, in a cohort of old age hip fractured patients by virtue of a timely osteo-metabolic and sarcopenic assessment. 98 patients consecutively enrolled at the IRCCS Hospital San martino, Genoa, Italy, received at baseline comprehensive geriatric assessment and Bone Densitometry (DXA) with the quantitative and quantitative bone analysis and evaluation of relative skeletal muscle index (RSMI) and longitudinally after 1 year form hip surgery. The results showed a slightly and non-significant osteo-metabolic improvement in the Alendronate group compared to the Denosumab group, and a positive trend of RSMI measurements in the Denosumab group Although preliminary in nature, this is the first report to longitudinally analyze osteosarcopenia in a real-world cohort of very old age patients after hip fracture and moved a step forward in the understanding of the best osteo-metabolic therapy for long- term treatment , exploring as well the potential dual role of denousumab as antiresorptive and muscle strength specific drug for osteosarcopenia in this vulnerable population.